2014
DOI: 10.1016/j.bandl.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of the insula in speech and language processing

Abstract: Lesion and neuroimaging studies indicate that the insula mediates motor aspects of speech production, specifically, articulatory control. Although it has direct connections to Broca's area, the canonical speech production region, the insula is also broadly connected with other speech and language centres, and may play a role in coordinating higher-order cognitive aspects of speech and language production. The extent of the insula's involvement in speech and language processing was assessed using the Activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
114
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(137 citation statements)
references
References 100 publications
10
114
0
1
Order By: Relevance
“…Although fMRI has yielded insights into the cortical mapping of speech, a shortcoming is that it cannot pinpoint regions that are crucial for speech-only areas that are correlated with a given speech processing task (25). It could be argued that careful metaanalysis studies that incorporate fMRI data may reveal converging evidence regarding the neural architecture that supports speech (26)(27)(28), but metaanalysis studies ultimately suffer the same shortcomings as basic fMRI studies: the inputs reflect task-associated cortical "activation" rather than areas of the cortex that need to be intact for successful speech processing.…”
Section: Significancementioning
confidence: 99%
“…Although fMRI has yielded insights into the cortical mapping of speech, a shortcoming is that it cannot pinpoint regions that are crucial for speech-only areas that are correlated with a given speech processing task (25). It could be argued that careful metaanalysis studies that incorporate fMRI data may reveal converging evidence regarding the neural architecture that supports speech (26)(27)(28), but metaanalysis studies ultimately suffer the same shortcomings as basic fMRI studies: the inputs reflect task-associated cortical "activation" rather than areas of the cortex that need to be intact for successful speech processing.…”
Section: Significancementioning
confidence: 99%
“…Language acquisition in humans is a tremendously complex process that involves a multitude of motor, sensory and cognitive domains (Oh et al, 2014). Therefore, it is not surprising to discover that a large variety of regions in the brain have been implicated in playing a role in language processing.…”
mentioning
confidence: 99%
“…The anterior insula has associations with a number of language related functions including phonological recognition, articulatory planning and language repetition ability (Ardila et al, 2014; Price, 2010). The insula is also uniquely positioned to serve as a potential coordinator of higher-order language processing, with direct connections to Broca’s area and other language centers (Oh et al, 2014). In addition, meta-analysis of PET and fMRI studies examining expressive language tasks has found that the insular cortex may serve as a functional relay between the motor and cognitive aspects of language (Eickhoff et al, 2009).…”
mentioning
confidence: 99%
“…However, its central location and connections with regions associated with a more diverse range of language functions including comprehension and lexico-semantic associations (Ardila et al, 2014) suggest that this region has an integral role in language processing (Price, 2010) and may mediate higher-order cognitive functions associated with language function (Oh et al, 2014).…”
Section: Relationship Between Subacute Brain Activity and Language Rementioning
confidence: 99%
“…The left insula is directly connected to Broca's region and has typically been considered to have an involvement in the motoric aspects of speech production and specifically articulatory planning (Ardila, Bernal, & Rosselli, 2014;Dronkers, 1996) and control (Oh, Duerden, & Pang, 2014).…”
Section: Relationship Between Subacute Brain Activity and Language Rementioning
confidence: 99%